Convergence and Divergence: Asymmetry in Higher Education Systems of Georgia and Europe - Ekaterina Zakaradze; Khatuna Muradishcili (European Scientific Journal, ESJ, 2026)
This article conducts a comparative analysis of the higher education systems in Georgia and the European Union, examining the dynamics of convergence and divergence within the framework of the Bologna Process and European integration agendas. The primary aim is to move beyond a superficial listing of similarities and differences to identify and analyze the structural, normative, and functional asymmetries that characterize this relationship. The study employs a qualitative mixed-methods approach, combining a review of policy documents and legislative frameworks with statistical data from Eurostat, the European University Association (EUA), and the National Centre for Educational Quality Enhancement of Georgia.The findings reveal a complex, dualistic landscape. On one hand, significant formal convergence is evident in structural reforms, such as the adoption of the three-cycle degree system, quality assurance mechanisms, and the ECTS. On the other hand, profound divergence and asymmetry persist in critical areas, including sustainable funding models, institutional autonomy, academic integrity, the practical implementation of quality assurance, and the integration into the European Research Area. The conclusion posits that while Georgia has successfully achieved formal alignment with European standards, substantive integration is hindered by a core-periphery dynamic. The article argues that overcoming this asymmetry requires not only continued policy compliance but also a dedicated focus on capacity building, resource allocation, and the cultivation of a robust academic culture to ensure a more equitable and synergistic partnership within the European Higher Education Area.